Most important factors modelling health status of an individual and the population. Part 2 - Jarosław Sobieszczański; Izabella Krupa; Anna Sobieszczańska; Halina Piecewicz-Szczęsna; Walery Zukow; Aleksandra Słopiecka (Kazimierz Wielki University, 2018)
Introduction Many factors exert an effect on the state of health, which are difficult to determine unequivocally, because many of them act together, and only a few occur independently. They also differ with respect to number and the degree of intensity. The diversification of these factors from the territorial aspect, both in Poland and worldwide, requires many actions coordinated by the agencies of international organizations, mainly the World Health Organization. In order to identify and shape the strength of individual and interdependent factors modelling of the state of health it is necessary to undertake further efforts to unify the definitions of health, disease, and disability.  In the whole scheme of medical care, the modelling of health status of an individual and the entire population is most important, in the area of actions for health promotion and prophylaxis, mainly on behalf of high quality programmes and the effectiveness of conducting these programmes. Objective The objective of the study was presentation of the significance of the selected health and social factors which may be of primary importance in maintaining and improvement of the state of health, both of an individual and the population. The detailed goals were: the discussion about these factors in the sphere of health promotion and anti-health behaviours, the level of health knowledge among the adult population and availability of health education, types of screening tests and determination of the trends in conducting studies in order to improve the health status and quality of life of an individual and the population.    Description of the state of knowledge The literature reports available show that several strategic problem groups, which form sub-groups, contribute to the factors shaping the level of human health, including life style and quality of life, hazards in the  physical environment, many natural and geographic factors, opportunities for health education, and the quality of care provided by health services. Qualitative and organizational actions of health care teams functioning in local environments are of special importance in the improvement of the quality of health status of an individual, family, and population. The major areas of actions which are a basis for the maintenance and enhancement of the state of health are health promotion and prophylaxis, as well as rehabilitation understood as a process of stages of actions. Reports are increasingly more often published concerning the modelling of the processes for diagnosing and evaluation of a patient's state of health. This is, among other things, the modelling of processes related with morbidity in cardiology, the concept of modelling of gossamer space structures in medical diagnosing and diagnosing of the health state of a patient, or the model of normalized life space with consideration of the selected health parameters. Summary Actions aimed at obtaining an improvement in the quality of modelling of the health status of an individual and the population should be based on systematic achievements in prevention studies, which provide possibilities for increasing control of own health of each person. A high quality of actions in the area of prophylaxis and health promotion may contribute to the selection of health promoting behaviours by increasingly larger population groups. An aware selection of such behaviours results in avoidance of risky behaviours, better skills in coping with stress, or selection of a pro-health life style. Efforts undertaken to increase pro-health knowledge lead to a systematic reduction in the incidence of so-called civilization diseases, which are currently a great public health problem.